(untitled) (Kinesiology, 2017)
The aim of this study was to compare the thoracic and lumbar curvatures and pelvic tilt in relaxed standing and maximal trunk flexion among highlytrained young athletes from three different sports disciplines. Thirty-two male canoeists, 30 male kayakers and 24 male tennis players were recruited for the study. The Spinal Mouse® system was used to measure the thoracic and lumbar sagittal spinal curvatures and pelvic tilt in relaxed standing and maximal trunk flexion in sitting with the flexed (McRae & Wright test) and extended knees (sit-and-reach test). Significant differences were found in maximal trunk flexion tests among athletes. Kayakers and canoeists showed increased anterior pelvic tilt compared to tennis players in the McRae & Wright (p<.01) and decreased posterior pelvic tilt in the sit-and-reach (p<.001) tests; however, canoeists had increased posterior pelvic tilt compared to kayakers in the sit-and-reach test (p<.01). Canoeists had increased thoracic kyphosis curvature compared to kayakers (p<.01) and tennis players (p<.001) in the sit-and-reach test. Spinal sagittal curvatures and pelvic tilt in relaxed standing did not show significant differences. In conclusion, specific sports training may be associated with adaptations in the sagittal spinal curvatures and pelvic tilt when maximal trunk flexion positions are performed. Key words: spine, thoracic curvature, lumbar curve, pelvic inclination, physical exercise